Pengaruh Augmented Reality Virtual Try On dan Electronic Word of Mouth Terhadap Keputusan Pembelian Lip Product Maybelline (Studi Pada Mahasiswa Universitas Negeri di Kota Medan): Penelitian - Ade Fadillah Harahap; Onan Marakali Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The objective of this study is to examine how the purchase of Maybelline lip products is influenced by Augmented Reality (AR) Virtual Try On and Electronic Word of Mouth (E-WOM), particularly among students at public universities in Medan City. This research is motivated by the rapid development of digital technology, which has transformed the way consumers interact with products. The study employed a quantitative associative approach, using a questionnaire as the instrument for data collection, with 96 respondents selected through purposive sampling. The results of the analysis demonstrate that AR and E-WOM have a positive and significant effect on purchasing decisions, both partially and simultaneously, contributing 57.5% to the variation in purchasing decisions. This research underscores the importance of digital communication and interactive technology in shaping modern consumer behavior.